2016
DOI: 10.1523/jneurosci.2631-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of Kv7.2/7.3 Cell Surface Dynamics at the Axon Initial Segment: High Steady-State Stability and Calpain-Dependent Excitotoxic Downregulation Revealed

Abstract: The voltage-gated K ϩ channels Kv7.2 and Kv7.3 are located at the axon initial segment (AIS) and exert strong control over action potential generation. Therefore, changes in their localization or cell surface numbers are likely to influence neuronal signaling. However, nothing is known about the cell surface dynamics of Kv7.2/7.3 at steady state or during short-term neuronal stimulation. This is primarily attributable to their membrane topology, which hampers extracellular epitope tagging. Here we circumvent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 12 publications
1
53
0
Order By: Relevance
“…On the other hand, rapid AIS plasticity as reported after significant elevation of neuronal activity in vitro seems to be driven by Ca 2+ signaling-related mechanisms and includes proteolysis in a calpain-dependent manner, which occurs on a much faster time scale of the disassembly of AIS proteins (Benned-Jensen et al, 2016;Evans et al, 2015;Evans et al, 2013;Schafer et al, 2009). Here, we found that rapid AIS plasticity occurs after a brief increase in activity during a behaviorally-relevant context in vivo, with AIS length reduction already 1 h after exposure to EE (Fig.…”
Section: Bidirectional Temporally Diverse Forms Of Ais Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, rapid AIS plasticity as reported after significant elevation of neuronal activity in vitro seems to be driven by Ca 2+ signaling-related mechanisms and includes proteolysis in a calpain-dependent manner, which occurs on a much faster time scale of the disassembly of AIS proteins (Benned-Jensen et al, 2016;Evans et al, 2015;Evans et al, 2013;Schafer et al, 2009). Here, we found that rapid AIS plasticity occurs after a brief increase in activity during a behaviorally-relevant context in vivo, with AIS length reduction already 1 h after exposure to EE (Fig.…”
Section: Bidirectional Temporally Diverse Forms Of Ais Plasticitymentioning
confidence: 99%
“…Our data so far suggest that AIS increases in length require long periods of deprivation (days to weeks). In contrast, studies applying depolarizing conditions in vitro showed that AIS length changes can be triggered more rapidly, within minutes to hours of increased in vitro network activity (Benned-Jensen et al, 2016;Evans et al, 2015). We next tested whether rapid AIS plasticity could be evoked in vivo in a behaviorally relevant context, by placing young adult wild type mice at P28 (n = 5-6 per group) to an enriched environment (EE) and expose whiskers to a larger range of novel stimuli.…”
Section: Ais Undergo Rapid Structural Plasticity After Induced Explormentioning
confidence: 99%
See 1 more Smart Citation
“…Under basal conditions, Kv7 channels have very low turnover rate throughout the axon [146]. However, surface expression of Kv7 channels is upregulated after neuronal stimulation [147].…”
Section: Surface Expressionmentioning
confidence: 99%
“…Indeed, a structurally intact AIS, with its specialized assembly of voltage-gated channels, cytoskeletal and associated proteins (Rasband, 2010) seems to be prerequisite to its normal function, as even relatively small plastic changes within the AIS (Grubb and Burrone, 2010;Kuba et al, 2010Kuba et al, , 2015Lezmy et al, 2017) elicit significant changes in neuronal excitability. Virtually all these proteins, including ␣and ␤-spectrins, ankyrins, Nav1.2, Nav1.6, and Kv7 channels, are either calpain substrates or subject to calpain-mediated endocytosis (Benned-Jensen et al, 2016). In the AIS, partial proteolysis and loss of anchoring of Na ϩ and K ϩ channels could render these channels nonfunctional and alter their distribution and biophysical properties (Iwata et al, 2004;von Reyn et al, 2012;Brocard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%